The Legal Nature and the Characteristic of the Main Categories of the Institute of Changing the Type of Correctional Facility for Imprisoned Convicts:Current State and Prospects of Development - Nikolai A. Tiufiakov (Сибирское юридическое обозрение, 2017)
In the article the main aspects of legal regulation of the institute of changing the type of correctional facility for imprisoned convicts are considered. According to the carried-out analysis changes in the criminal and criminal and executive legislation of the Russian Federation are offered.